Association Study of GABAA α2 Receptor Subunit Gene Variants in Antipsychotic-Associated Weight Gain. Issue 1 (February 2015) - Zai, Clement C.H.; Tiwari, Arun K.; Chowdhury, Nabilah I.; Brandl, Eva J.; Shaikh, Sajid A.; Freeman, Natalie; Lieberman, Jeffrey A.; Meltzer, Herbert Y.; Müller, Daniel J.; Kennedy, James L.
<x xml:space="preserve">Abstract</x> Abstract Schizophrenia treatment has been hampered by undesirable adverse effects, including weight gain and associated complications. Recent candidate gene studies have been exploring the appetite regulation pathways in antipsychotic-associated weight gain (AAWG) with some promising leads. Genome-wide association studies of obesity have pointed to a number of potential candidate genes, such as MC4R, that were later found to be shared with AAWG. GABAA α2 receptor subunit (GABRA2) was another potential candidate gene for obesity from genome-wide association studies; however, it has not been explored in AAWG. We examined 9 single nucleotide polymorphisms across the GABRA2 gene. Prospective weight change was assessed for a total of 160 schizophrenia patients of European ancestry. The rs279858 marker was associated with percent weight change, with the patients homozygous for the TT genotype experiencing higher percentage weight gain on average than the C allele carriers (P = 0.009). When we performed the analysis considering each clinical site using a meta-analytic method, the results remained statistically significant (P = 1.4e−4). These findings became even more significant when we considered only patients taking clozapine or olanzapine, the 2 medications with higher risk for weight gain (P < 1e−10). GABRA2 genetic variants may play a role in predicting AAWG. However, replication in larger and independent samples is required.